2011
DOI: 10.3174/ajnr.a2751
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Diastolic Sonoelastographic Scoring in the Management of Thyroid Nodules

Abstract: SUMMARY:We determined that the application of a 5-point scoring method by using an external manual compression method synchronized with the diastolic period of the carotid artery by sonoelastography was helpful in the management of thyroid nodules. The mean scores on sonoelastography were 2.74 Ϯ 0.97 for 62 benign nodules and 3.90 Ϯ 0.88 for 10 malignant nodules (P Ͻ .01). Eighty-seven percent of benign nodules were determined when a cutoff point between scores 3 and 4 was used.ABBREVIATIONS: FNAB ϭ fine-needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Qualitative elastography has been described as a promising new technique in differentiating benign from malignant thyroid nodules [30][31][32][33][34][35][36][37][38][39][40][41][42]. The aim of this systematic review and metaanalysis was to investigate the diagnostic value of qualitative elastography in distinguishing benign from malignant thyroid nodules in patients referred for FNA and, thereby, potentially prevent unnecessary invasive diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative elastography has been described as a promising new technique in differentiating benign from malignant thyroid nodules [30][31][32][33][34][35][36][37][38][39][40][41][42]. The aim of this systematic review and metaanalysis was to investigate the diagnostic value of qualitative elastography in distinguishing benign from malignant thyroid nodules in patients referred for FNA and, thereby, potentially prevent unnecessary invasive diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous studies have showed that strain elastography has the potential for differentiating between benign and malignant thyroid nodules, whereas its sensitivity and specificity varied from 73% to 100% and 50% to 96% respectively. [10][11][12][13][14][15] Strain elastography is usually qualitative or semiquantitative and is generated by manual compression, which is dependent on the experience of the operator and thus is less reproducible. Shear wave elastography is a quantitative elastographic technology for transverse shear wave velocity (SWV) measurement and imaging using acoustic radiation force impulse excitation, which includes point SWE and 2dimensional (2D) SWE.…”
Section: College Of Radiology Breast Imaging Reporting and Datamentioning
confidence: 99%
“…The hardness of tissues or lesions is visually and qualitatively assessed on the basis of the strain distribution and pattern of elastographic images. 1,[6][7][8][9][10]12,[15][16][17][19][20][21][22][23][24] Semi-quantitative analysis, in which strain is represented in numerical values, has recently been used as a more objective method. [1][2][3][4][5][9][10][11]13,17 However, whether these values can be effectively used for clinical assessment remains unclear because the image quality of strain elastography, which is performed manually, depends strongly on the imaging procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been used to assess the hardness of various normal and abnormal tissues, [1][2][3][4][5][6] and to differentiate malignant from benign lesions in the breast, prostate, thyroid, lymph nodes and salivary glands. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ultrasound elastography uses either strain or shear wave velocity. 25,26 In strain elastography, tissue strain induced by compression with the probe is used as an indicator of hardness.…”
Section: Introductionmentioning
confidence: 99%